Health and the Millennium Development Goals (WHO GenevaCH, 2005)
Explains some of the reasons for the slow progress in achieving the goals and suggests solutions. Discusses strategic and policy areas where change is needed and support should be provided. Summarizes WHO's contribution to debates on the MDGs and to the 2005 World Summit.
Keywords: HEALTH